The Urge to Merge: Ritual Insult and the Evolution of Syntax - Ljiljana Progovac; John L. Locke (Biolinguistics, 2009)
Throughout recorded history, sexually mature males have issued humorous insults in public. These ‘verbal duels’ are thought to discharge aggressive dispositions, and to provide a way to compete for status and mating opportunities without risking physical altercations. But, is there evidence that such verbal duels, and sexual selection in general, played any role in the evolution of specific principles of language, syntax in particular? In this paper, concrete linguistic data and analysis will be presented which indeed point to that conclusion. The prospect will be examined that an intermediate form of ‘proto-syntax’, involving ‘proto-Merge’, evolved in a context of ritual insult. This form, referred to as exocentric compound, can be seen as a ‘living fossil’ of this stage of proto-syntax — providing evidence not only of ancient structure (syntax/semantics), but also arguably of sexual selection.